Analisis faktor-faktor yang mempengaruhi praktik ibadah mahasiswa taklim UII menggunakan regresi logistik ordinal - Rachman, Kireina Delva; Intiari, Venti Diah; Khairunnisa, Rizka; Kurniati, Nur Mahmudah; Chantika, Shevina Nita Rahma; Kariyam, Kariyam (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
One of the goals of the birth of the Islamic University of Indonesia (UII) is to make its alumni as Muslim scholars who have the ability in the field of science they practice, especially each individual UII alumni must master, understand, practice and preach Islam which is the hallmark of UII in practicing principles, scientific knowledge. amaliah, do good deeds. It was realized that it was difficult to carry out a process of internalizing religious material without the support of the awareness of all parties, both educative, administrative, leadership of the faculty, and university institutions, as well as awareness of the students themselves. Students as a component to be fostered become one of the benchmarks of success of a series of non-curricular coaching programs ranging from ONDI, pesantrenisasi stage 1,2, LKID, LKIM, LKIL, and Ta'lim (PDQ). The urgency of this religious guidance cannot be denied because various data show that the level of religious understanding of students is very poorly obtained based on the UII quality objectives for the non-curricular religious guidance program that all students graduate with a good grade of 80%. One of the Qur'an self-improvement programs in the form of ta'lim (Islamic religious assistance) that must be followed by students starts for four semesters with a progress report every semester. However, in the implementation of the regimes it is possible to create obstacles. To find out the factors that influence the effectiveness of taklim programs in terms of religious practices, an influence analysis is done using ordinal regression.